Penyuluhan Nilai-Nilai Pancasila dan Toleransi Terhadap Siswa Usia Dini melalui Literasi Digital - Firmananda, Fahmi Iqbal; Ependi, Zulfan; Sumianto, Sumianto; Jati, Putri Zulia; Rianita, Resti (Journal of Digital Community Services, 2024)
Instilling Pancasila values and tolerance towards young students is an important thing to do, especially in the current digital era. This is because young students are the nation's next generation who are vulnerable to the influence of radicalism and terrorism. Radicalism and terrorism are serious threats to the integrity of the nation and state. The current digital era makes it easier to spread radicalism and terrorism. Early age students who actively use social media are vulnerable to being exposed to these ideas. Therefore, it is important to equip young students with adequate digital literacy so they can use social media wisely and avoid the influence of radicalism and terrorism. Based on the results of observations, MI Al Wathaniyah students' understanding of the importance of digital literacy in preventing radicalism and terrorism is still low. Students do not clearly understand what digital literacy is and how digital literacy can be used to prevent radicalism and terrorism. This community service activity aims to increase the digital literacy of MI Al Wathaniyah students in preventing radicalism and terrorism. This activity was carried out in two stages. The first stage is education about the importance of digital literacy in preventing radicalism and terrorism. The second stage is the practice of using digital literacy for learning about Pancasila and tolerance. Counseling material about the importance of digital literacy in preventing radicalism and terrorism includes: Understanding digital literacy The importance of digital literacy in everyday life How to use digital literacy wisely The dangers of radicalism and terrorism How to prevent radicalism and terrorism Practical material for using digital literacy for learning about Pancasila and tolerance include: Using social media to search for information about Pancasila and tolerance Making posters or videos about Pancasila and tolerance The results of this community service activity show that MI Al Wathaniyah students have a fairly good understanding of the importance of digital literacy in preventing radicalism and terrorism. Students can also use digital literacy to learn about Pancasila and tolerance well.